Exchange rates, monetary policy and wages: A case study of Chile - David P. Vincent (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
This paper analyses, using a comparative-static general equilibrium model built along neoclassical lines, a range of devaluation, monetary and wage policy mixes for the Chilean economy. By quantifying the short-run implications of each policy mix for key economic variables at the macroeconomic and sectoral level it enables judgements to be made about their effectiveness in reaching specified targets and their feasibility.
Keywords: 330